Bicycle Tourism in Konya Tourism Perspective And A Study On Its Effect On Marketing Konya Tourism As A Destination By Using PEST Analysis - Osman Ünüvar; Mürsel Kaya; Mete Sezgin (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
Tourism is an important sector that its importance has globally been being understood day by day and has continuously been received quite much investment. It is obvious that it became an area of vital activity for Turkey and Konya in near past. The target of this study is to reveal the potential, its execution area and its contribution of bicycle tourism on Konya tourism. It has been considered that bicycle tourism, a new model of sustainability and diversification, will make a great contribution in city culture and Konya tourism in progress of time. To popularize using bicycle will prevent the young from harmful habits (smoking, alcohol, drug addiction etc.), and it will contribute in solving some serious and basic problems nowadays like obesity and stress, environment, traffic, public transportation and improving tourism and promoting Konya tourism by bringing touristic values into forefront. It has been considered that local administration’s efforts to improve the substructure for sportive activities in Konya having suitable topographic features for using bicycle deserve admiration. In this context, the bicycle routes and tourism subjects around Konya will have the opportunity of being promoted divergently by dealing Konya tourism potential and considering this potential having different presentation via bicycle tourism. Another inference about bicycle tourism is that it will strengthen and contribute in social networking and interaction among different social stratums as a result of using bicycle as an integrative tool for society.